Induction of cell death in prostate cancer cells by escopoletin, a promising treatment strategy - Da Chen; Xiao-Yi Zhang; Fa-Zhu Zheng; Hai-Tao Wang; Jian-Liang Cai; Ming Xia (Bangladesh Pharmacological Society, 2015)
Escopoletin, a phenolic compound belonging to anthocyanin family shows promising antioxidant activities. In the present study, anti-cancer effects of escopoletin treatment in DU145 cells were investigated. The sulphorhodamine-B staining and annexin V and propidium iodide were respectively used for the analysis of cell viability and death. The results revealed a significantly higher cytotoxicity by escopoletin that caused cell death in DU145 cells. Escopoletin treatment in DU145 cells markedly inhibited cell growth through non-apoptotic cell death and induced significant reactive oxygen species (ROS) production. It also induced G1 cell cycle arrest and cyclin D1 accumulation through the enhanced expression of p21. However, the effect of escopoletin on DU145 cells was reversed by pretreatment with glutathione antioxidant. This suggests that escopoletin induced generation of ROS is responsible for the increased cytotoxicity in DU145 cells. Thus, escopoletin exhibits potential therapeutic efficacy for the treatment of prostate cancer.